Reservoir monitoring using streaming potential; is the thermoelectric correction necessary? - Jaafar, Mohd. Zaidi (2015)
Wellbore streaming current and their applicability in the location of subsurface sand bodies were discovered in 1931 and the usefulness of this measurement has persisted to the present day. Through the endeavor of many researchers, knowledge and understanding of streaming potential (SP) have slowly evolved from the original mere recognition of its existence to its present-day quantitative use in many applications such as Enhanced Oil Recovery (EOR), water flooding, intelligent wells, etc. The spontaneous potential acts to maintain overall electroneutrality when a separation of electrical charge occurs in response to gradients in pressure (Electrokinetic), chemical composition (Electrochemical), or temperature (Thermoelectric). In spite of it being discovered 70 years ago, unfortunately little work has been done to find measurable value especially for thermoelectric coupling coefficient. Many researchers attempt to generate a universal model for SP. They attributes the limitations (if any) of their model to the scarce availability of accurate estimation for coupling coefficient. This study measures the value of thermoelectric coupling coefficient for five rock samples saturated with 0.01M (NaCl) saline brine. The study takes account of temperature dependant electrode effect. The result shows value of 0.2 mV/K, which is in a good match with most of the published data. It was also found that there is no strong correlation between the thermoelectric coupling coefficient and porosity. The measured thermoelectric values are considered insignificantly small compared to the electrokinetic effect in the system.